2016
DOI: 10.1177/0192623316650050
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Exacerbation of Light-induced Retinal Degeneration in F344/N Rats in National Toxicology Program Rodent Bioassays

Abstract: Retinal degeneration due to chronic ambient light exposure is a common spontaneous age-related finding in albino rats, but it can also be related to exposures associated with environmental chemicals and drugs. Typically, light induced retinal degeneration has a central/hemispherical localization where as chemical induced retinal degeneration has a diffuse localization. This study was conducted to identify National Toxicology Program (NTP) rodent bioassays with treatment-related retinal degeneration, and to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
8
0
2
Order By: Relevance
“…Pramipexole dihydrochloride, a dopamine agonist, induces retinal degeneration in albino rats by reducing the rate of phagocytosis, and its severity is increased by enhanced light intensity (FDA 1997a(FDA , 2013. A retrospective evaluation of rat retinas from the 2-year NTP KKE bioassay indicated that chronic KKE exposure exacerbated light-induced retinal degeneration since the frequency of retinal degeneration was increased in a dose-dependent manner and the distribution and morphology (but not severity) of retinal degeneration was similar to the changes observed in light-induced retinal degeneration reported in albino rats (Yamashita et al 2016). In this study, phagocytosis of photoreceptor outer segment was decreased only in the superior retina, which is more sensitive to light damage than the inferior retina (Tanito et al 2008).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Pramipexole dihydrochloride, a dopamine agonist, induces retinal degeneration in albino rats by reducing the rate of phagocytosis, and its severity is increased by enhanced light intensity (FDA 1997a(FDA , 2013. A retrospective evaluation of rat retinas from the 2-year NTP KKE bioassay indicated that chronic KKE exposure exacerbated light-induced retinal degeneration since the frequency of retinal degeneration was increased in a dose-dependent manner and the distribution and morphology (but not severity) of retinal degeneration was similar to the changes observed in light-induced retinal degeneration reported in albino rats (Yamashita et al 2016). In this study, phagocytosis of photoreceptor outer segment was decreased only in the superior retina, which is more sensitive to light damage than the inferior retina (Tanito et al 2008).…”
Section: Discussionmentioning
confidence: 81%
“…The degeneration consisted of a thinning and loss of the external retinal layers, such as the photoreceptors and external nuclear layers, with a decreased cellularity and disorganization of the remaining retinal layers (NTP 2012). A retrospective evaluation of rat retinas from the 2-year NTP KKE bioassay indicated the distribution and morphology of retinal degeneration was similar to the changes observed in light-induced retinal degeneration reported in albino rats (Yamashita et al 2016). Therefore, it was hypothesized that KKE has the potential to exacerbate the lightinduced retinal degeneration.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…У пигментированных животных после длительного воздействия света не обнаруживаются какие-либо морфологические изменения, в то время как у альбиносов развивается дегенерация сетчатки. Интересным является тот факт, что воздействие света может дополнитель- но усиливать дегенеративные процессы в сетчатке как у химически-индуцированных моделей, так и у генетических моделей [29,40,41,48].…”
Section: индуцированные модели дегенерации сетчаткиunclassified
“…Retinal degeneration due to light exposure is a common spontaneous finding in albino rodents. However, the finding can be seen as a xenobiotic-induced exacerbation (Yamashita et al ., 2016). In general, light-induced retinal degeneration is manifested as localized lesion and is limited to superior-temporal regions, especially when not in the advanced stage of lesion development; whereas xenobiotic induced retinal degeneration is more diffuse (De Vera Mudry et al ., 2013).…”
Section: Adaptive Non-adverse and Adverse Responses In Non-clinmentioning
confidence: 99%